A liver transplant recipient with possible bupivacaine-induced liver injury caused by intra-articular injection after total knee arthroplasty: A case report. Issue 38 (September 2018) - Lee, Jeong Eun; Kwak, Kyung-Hwa
Abstract: Rationale: Although the survival period of patients who undergo liver transplantation is improving due to advances in surgical techniques and medical treatment, there is a lack of detailed, sufficient data that compare the choice of anesthetic agent in post-liver transplant surgery to avoid liver injury. Patient concerns: The authors describe acute liver injury observed in a 61-year-old man who underwent liver transplantation surgery 13 years previously and who was on immunosuppressive therapy. The patient underwent bilateral total knee arthroplasty under general anesthesia, for which a total of 200 mg bupivacaine was injected into each knee after wound closure. Liver enzyme levels increased to more than 10 times the upper limit of normal after the conclusion of surgery and remained extremely high on postoperative day 1. Diagnoses: Clinical and laboratory findings were consistent with bupivacaine-induced liver injury. Intra-articular administration of bupivacaine after total knee arthroplasty is a widely used intraoperative analgesic method and complications are rare; nevertheless, the risk for inadvertent delivery into the systemic circulation remains. Interventions: Clinical presentations and hepatobiliary ultrasound examination allowed a conservative management. Outcomes: Serum liver enzyme levels normalized 12 days after surgery, and the patient was discharged 22 days after surgery. Lessons: Acute liver injury can lead to graft failure from late death after liver transplantation. Transplant recipients with long-term survival have the highest risk for anesthesia because of post-transplant complications, including diabetes, hypertension, and renal insufficiency. Clinicians should be aware that analgesic techniques and anesthetics may affect graft function.